2014
DOI: 10.1111/1346-8138.12569
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐C*12:02 is a susceptibility factor in late‐onset type of psoriasis in Japanese

Abstract: Psoriasis is thought to be a multifactorial disease triggered by both genetic and environmental factors. The HLA-C locus on chromosome 6p21.33 remains the strongest susceptibility candidate locus in psoriasis. The strong association between psoriasis and the HLA-Cw6 allele has been well documented in various races. It is known that psoriatic patients with early onset are more likely to be familial and associated with HLA-Cw6. Familial occurrence of Japanese psoriasis is smaller than other populations. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…This highlights the need to use population-specific reference panels made by deep sequencing to impute MHC alleles and amino acids ( 8 ). The strong psoriasis risk of HLA-C*06:02 allele has been validated in worldwide populations including Europeans ( 17 , 20 ), East ( 6 , 21 ), and South Asians ( 22 ), with odds ratios of as high as 3.0–10.0. HLA fine-mapping analysis using the HLA imputation method successfully identified multiple other less obviously associated HLA-class I and class II variants that confer psoriasis risk independently from HLA-C*06:02 ( 20 ).…”
Section: Hla-class I Association Of Psoriasis: the Main Genetic Riskmentioning
confidence: 99%
“…This highlights the need to use population-specific reference panels made by deep sequencing to impute MHC alleles and amino acids ( 8 ). The strong psoriasis risk of HLA-C*06:02 allele has been validated in worldwide populations including Europeans ( 17 , 20 ), East ( 6 , 21 ), and South Asians ( 22 ), with odds ratios of as high as 3.0–10.0. HLA fine-mapping analysis using the HLA imputation method successfully identified multiple other less obviously associated HLA-class I and class II variants that confer psoriasis risk independently from HLA-C*06:02 ( 20 ).…”
Section: Hla-class I Association Of Psoriasis: the Main Genetic Riskmentioning
confidence: 99%
“…As mentioned above, psoriasis is a chronic inflammatory skin disease driven by the TNF-α/IL-23/IL-17 axis (1, 4, 10). This notion is well supported by the high clinical efficacy of biologics against the TNF-α/IL-23/IL-17 pathway (5, 8, 15, 66).…”
Section: Pathophysiology Of Comorbiditymentioning
confidence: 99%
“…More than 36 genetic loci are associated with psoriasis, 1 and of these, HLA-C * 06, also known as HLA-Cw6 or PSORS1 (6p21.33), has the strongest disease association. 2 4 HLA-Cw6+ patients tend to have an earlier onset of disease and more severe manifestations. 5 8 Previous studies have suggested that HLA-Cw6 genotyping could possibly play a role in predicting therapy outcome to the interleukin-12/23 antagonist, ustekinumab, making pharmacogenomics a promising field of research.…”
Section: Introductionmentioning
confidence: 99%